KARAKTERISTIK IBU YANG TIDAK MEMBERIKAN ASI EKSKLUSIF - Muryati, Muryati; Widyastuti, Yani; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2015)
Baby food and children are critical to improving child survival and promote healthy growth and development of promotive and preventive efforts to prevent deaths and improve children's intelligence have been carried out, showing that breastfeeding is the best way to decrease the mortality of children under five. Sleman PHC is one of the health centers in the district of SIeman the number of infants who are exclusively breastfed lows in 2011 is 38.30%. Order to determine the characteristics of mothers who did not breastfeed exclusively at PHC Sleman 2012. Type a descriptive study with a cross-sectional design. The population in this study is that all mothers of infants aged 6-12 months are not exclusive breastfeeding at Puskesmas Sleman in 2012. In this study using a study population that was not done sampling. Maternal characteristics are based on education, employment, parity, and age. The data analysis using descriptive analysis techniques with relative frequency distribution method. Result: Women who are not exclusively breastfed majority of primary education (48%), work status (86.7%), parity 1 (41%), and unhealthy reproductive age (63.3%).